2017
DOI: 10.1021/acs.jcim.7b00258
|View full text |Cite
|
Sign up to set email alerts
|

Digitizing Poly-l-lysine Dendrigrafts: From Experimental Data to Molecular Dynamics Simulations

Abstract: Despite the growing use of poly-l-lysine dendrigrafts in biomedical applications, a deeper understanding of the molecular level properties of these macromolecules is missing. Herein, we report a simple methodology for the construction of three-dimensional structures of poly-l-lysine dendrigrafts and the subsequent investigation of their structural features using microsecond molecular dynamics simulations. This methodology relies on the encoding of the polymers' experimental characterizations (i.e., composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…[9] One may assume that it resultsf rom ak inetic control linked to steric hindrance between the growing chains, as well as at hermodynamic control linked to the precipitation of the protected polymers in water.S ince DGLs are made of l-lysine residues,t hey could initially be assimilated to proteins. [16] In addition, microsecond molecular dy-namics simulations on DGLs G1-G4 revealed that the dendrigrafts adopt intermediate morphologies betweenD PLs and LPLs, which may remind those of unfolded and intrinsically disorderedp roteins. [16] In addition, microsecond molecular dy-namics simulations on DGLs G1-G4 revealed that the dendrigrafts adopt intermediate morphologies betweenD PLs and LPLs, which may remind those of unfolded and intrinsically disorderedp roteins.…”
Section: Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] One may assume that it resultsf rom ak inetic control linked to steric hindrance between the growing chains, as well as at hermodynamic control linked to the precipitation of the protected polymers in water.S ince DGLs are made of l-lysine residues,t hey could initially be assimilated to proteins. [16] In addition, microsecond molecular dy-namics simulations on DGLs G1-G4 revealed that the dendrigrafts adopt intermediate morphologies betweenD PLs and LPLs, which may remind those of unfolded and intrinsically disorderedp roteins. [16] In addition, microsecond molecular dy-namics simulations on DGLs G1-G4 revealed that the dendrigrafts adopt intermediate morphologies betweenD PLs and LPLs, which may remind those of unfolded and intrinsically disorderedp roteins.…”
Section: Characterizationmentioning
confidence: 99%
“…Various analytical techniques were used to extensively characterize the poly-l-lysine dendrigrafts, including NMR spectrometry, [12] dynamic light scattering, Ta ylor dispersion analysis, size Synthetic routet oward first-to fourth-generation DGLs G1-G4,and their respective schematic representation (eachdot represents a l-lysine residue, pending free amino groups are not represented).The synthesis of each generation involves the following sequence:polycondensation in water,centrifugation for collecting the precipitate, alkaline deprotection of the side chains, and concentration in vacuo. exclusion chromatography, [13] refractometry, [14] capillary isotachophoresis, [15] potentiometry, [16] colorimetry, [17] cyclic voltammetry, [18] and Ramans pectroscopy. [19] Ta ble 1g athers few selected physicochemical properties for DGLs G1-G4.I ts hould be highlighted that such as imple synthetic procedure exerts an unexpected control on the molecular weighta nd diversity of the resulting dendrigrafts.I ndeed, poly-dispersity indexes measured for DGLs (1.20-1.46) are below those of both LPLs and HPLs( 1.3-2.6 and 1.8-2.6,r espectively), and are comparable to those of genuine DPLs (1.1-1.5), which are only accessible through al aboriousm ultistep process.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of a smaller net charge of the G4 PAMAM dendrimer than that of DGL-G3, the ∆G D⋅⋅⋅ANS values indicate the relatively stable association of ANS − with the G4 PAMAM dendrimer: DGL-G4−ANS > G4 PAMAM−ANS > DGL-G3−ANS > DGL-G2−ANS. A recent report by Francoia et al suggested that the polyelectrolyte effect totally prevents the protonation of α-amino groups of DGL at a physiological pH 9. Although the α-amino groups of the DGL could be partly protonated under neutral pH conditions, the ε-amino groups are mainly responsible for the electrostatic interaction with guest anions.…”
mentioning
confidence: 99%